(untitled) (World Economics and Finance Bulletin, 2025)
Electronic marketing is considered one of the fundamental methods that have helped institutions, including banks, adapt to modern economic and technological changes. It has enabled them to communicate with a large number of customers, understand their behaviors and needs, which in turn has helped improve services and increase customer engagement and loyalty. With fierce competition, especially in the banking sector, electronic marketing has become an effective means to distinguish banks, enhance their market position, and sustain growth in an environment characterized by rapid change and globalization. Electronic marketing is considered one of the fundamental methods that have helped institutions, including banks, adapt to modern economic and technological changes. It has enabled them to communicate with a large number of customers, understand their behaviors and needs, which in turn has helped improve services and increase customer engagement and loyalty. With fierce competition, especially in the banking sector, electronic marketing has become an effective means to distinguish banks, enhance their market position, and sustain growth in an environment characterized by rapid change and globalization.